Allocation of Internal Cash Flow when Firms Pay Less Tax - Guenther, David A.; Njoroge, Kenneth; Williams, Brian M. (The Accounting Review, 2020)
ABSTRACT We provide evidence about allocations of cash flow freed up by not paying taxes (“tax-related cash”). Uncertainty about future repayments suggests firms may use tax-related cash more cautiously than other cash flow. We utilize a flow-of-funds model from finance to quantify the relative amounts of tax-related cash associated with various potential uses of operating cash flow. We find firms allocate tax-related cash differently than other after-tax cash flow. Prior studies find tax avoiders hold more cash, and our results suggest this is because firms invest less (and save more) tax-related cash. We also find that the allocation of tax-related cash varies with relative financial constraints, economic uncertainty, and firms' multinational status in ways consistent with prior findings. For example, firms facing relatively higher levels of financial constraints invest a lower (higher) percentage of tax-related cash in capital expenditures (marketable securities and R&D), possibly to preserve funds for future investment opportunities. JEL Classifications: G31; H20.